Occurrence of Cronobacter spp. (Enterobacter sakazakii) in infant food purchased in a public hospital - Freitas, Luciana Giorgetti (2011)
Cronobater spp. (E. sakazakii) is considered an opportunistic pathogen and the public health authorities have given attention to this matter because of the increasing number of infection outbreaks in neonates and infants. The bacterium is associated with rare cases which can cause meningitis, necrotizing enterocolitis and septicemia, with a high mortality rate. Cronobacter spp. is widely disseminated, but only the powdered infant milk formulas were epidemiologically linked to diseases caused by this agent. The aim of this study was to evaluate the occurrence of Cronobacter spp. in foods for children aged 0-36 months, that were purchased in a public hospital in São Paulo. Twenty six reconstituted samples and 24 powdered formulas were analyzed according to the methodology established by ISO. Cronobacter spp. was detected in one sample (3.8%) of reconstituted infant food based on corn flour and in other four samples (16.7%) of these powered products . The bacterium was not detected in infant formula for children aged 0-6 months, although its presence in baby food might contribute to contaminate the lactary environment and devices by cross-contamination.